Performance modulation through selective, homogenous surface doping of lanthanum strontium ferrite electrodes revealed by in situ PLD impedance measurements. Issue 6 (22nd December 2021) - Riedl, Christoph; Siebenhofer, Matthäus; Nenning, Andreas; Friedbacher, Gernot; Weiss, Maximilian; Rameshan, Christoph; Bernardi, Johannes; Limbeck, Andreas; Kubicek, Markus; Opitz, Alexander Karl; Fleig, Juergen
Abstract : The polarization resistance of lanthanum strontium ferrite thin film electrodes with and without additional Pt surface doping was compared directly after film growth by PLD employing in situ electrochemical impedance spectroscopy. Abstract : Accelerating the oxygen reduction kinetics of solid oxide fuel cell (SOFC) cathodes is crucial to improve their efficiency and thus to provide the basis for an economically feasible application of intermediate temperature SOFCs. In this work, minor amounts of Pt were doped into lanthanum strontium ferrite (LSF) thin film electrodes to modulate the material's oxygen exchange performance. Surprisingly, Pt was found to be incorporated on the B-site of the perovskite electrode as non metallic Pt 4+ . The polarization resistance of LSF thin film electrodes with and without additional Pt surface doping was compared directly after film growth employing in situ electrochemical impedance spectroscopy inside a PLD chamber ( i -PLD). This technique enables observation of the polarization resistance of pristine electrodes unaltered by degradation or any external contamination of the electrode surface. Moreover, growth of multi-layers of materials with different compositions on the very same single crystalline electrolyte substrate combined with in situ impedance measurements allow excellent comparability of different materials. Even a 5 nm layer of Pt doped LSF (1.5 at% Pt), i.e. a Pt loading of 80 ng cm −2, improved the polarization resistance by a factor of about 2.5. In addition, p (O2 ) and temperature dependent impedance measurements on both pure and Pt doped LSF were performed in situ and obtained similar activation energies and p (O2 ) dependence of the polarization resistance, which allow us to make far reaching mechanistic conclusions indicating that Pt 4+ introduces additional active sites.